Pengaruh Kualitas Pelayanan Kinerja BUMDES terhadap Pemberdayaan Masyarakat Desa Pungpungan Kabupaten Bojonegoro - Kustaji; Anggapratama, Reza; Niswah, Syifa’un (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The Village-Owned Enterprise (BUMDes) of Pungpungan Village, Bojonegoro Regency, represents a form of village business entity that plays a crucial role in stimulating the local economy and enhancing community welfare. In its operational activities, BUMDes encounters various challenges in delivering high-quality services to optimally support the community empowerment process. Therefore, it is necessary to conduct research to examine the extent to which BUMDes service quality influences the level of community empowerment. This study employed a quantitative method with a survey approach and multiple linear regression analysis technique. The findings indicate that the performance indicators of BUMDes service quality simultaneously have a significant effect on community empowerment. Service quality variables, including tangibles, reliability, responsiveness, assurance, and empathy, collectively account for 54.4% of the variation in community empowerment, while the remaining 45.6% is attributed to other factors. It is imperative for BUMDes Pungpungan Village to enhance its service quality through capacity building, performance evaluations, and a more responsive approach to community needs.